PENGARUH KOMBINASI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL JAHE MERAH - Astuti, Puji (Fakultas Pertanian Universitas Tanjungpura, 2019)
A Red ginger (Zingiber officinale Rosc.) is a herbal plant that is cultivated by farmers to meet the raw material of medicine industry and conserve the living environment. It contains various chemical substances such as essential oil and oleoresin (gingerol, zingeron, shogaol, and resin). The purpose of this study was to determine the effect of the combination treatment of rice husk charcoal, chicken manure, cocopeat, and alluvial soil on the growth and yield of red ginger plants and to determine which combination of planting media treatment could provide the best red ginger. This research was conducted in an experimental design arranged based on a Complete Random Design (RAL), with one treatment factor, namely a combination of planting media (P). Therefore, there were 7 combination treatments and each treatment repeated for three 4 times. Every experimental unit has 3 samples of plants. So, there are 84 samples of plants in the polybag. The variables observed were plant height, leaf area, leaf chlorophyll, number of leaves, number of tillers, rhizome weight per clump, and dry weight of plant. The results of the analysis show that various combinations of planting media have no significant effect on the observation variables Leaves, Leaf Chlorophyll, Leaf Area, Rhizome weight per clump, dry weight of plant, Plant Height 4 MST, 8 MST, and 12 MST and significantly influence the number of tillers. The results showed that in the combination treatment of soil planting media : rice husk charcoal : chicken manure with a ratio of 1: 1: 1 significantly affected the number of tillers.Keywords: Alluvial, Red Ginger, and Planting Media Combination.